Preparation and Quality Evaluation of Flaxseed Incorporated Cereal (Oat) Bar - Subedi, Binita; Upadhyaya, Nawaraj (Journal of Food Science and Technology Nepal, 2019)
A study was carried out to prepare cereal bars incorporated with flaxseed rich in nutritional and sensory characteristics which are convenient to carry and consume as a snack. Full fat roasted flaxseed flour was incorporated along with commercially available instant oat flakes at the rate of 5, 10, 15 and 20% to prepare Cereal (Oat) bar. Effect of flaxseed flour incorporation was studied in proximate composition, calcium, iron and phosphorus content of cereal bar. The addition of flaxseed flour increased (p<0.05) the nutritional value of the cereal bar in terms of crude protein, crude fat, crude fiber and total ash however, the carbohydrate content significantly decreased. Sensory evaluation of cereal bars were carried out in terms of appearance, color, odor, taste, texture and overall acceptability. Cereal (Oat) Bar prepared by incorporating 10% flaxseed flour was found to be significantly (p<0.05) superior from sample with no flaxseed flour in terms of texture and overall acceptability.